An element subscale refinement for representation of the progressive fracture based on the phantom node approach. (February 2018) - Mostofizadeh, S.; van der Meer, F.P.; Fagerström, M.; Sluys, L.J.; Larsson, R.
Abstract: A new approach for the analysis of the ductile fracture of thin-walled large scale structures is developed. The method proposes a subscale refinement of the elements containing the crack. It allows for smooth progression of the crack without furnishing required level of the mesh refinement, and a more detailed representation of the crack tip and crack kink within the cracked elements. This approach is based on the phantom node method and is intended to be applicable for different types of elements including both low and high order elements. Numerical examples for dynamic crack propagation are presented and compared to conventional solutions to prove the accuracy and effectiveness of the proposed approach.